The Determination and Analysis of Factors Affecting to Student Learning by Artificial Intelligence in Higher Education - Ozbey, Nigar; Karakose, Mehmet; Ucar, Aysegul (Ieee, 2016)
At the present time, with the improvement of educational work in the education field life, and is intended to facilitate the organization. Many methods are used to accomplish this goal. Artificial intelligence is one of these methods. With artificial intelligence applications to problems encountered in the educational life solutions are the way. In this study, an analysis of the factors affecting student learning and the identification process is carried out by an artificial intelligence-based method. An optimization method for determining the factors affecting the learning process has been proposed. Because many factors that are effective for student learning. For this reason the optimization process must be performed of these factors. An optimization process using fuzzy logic and genetic algorithm is proposed to perform this operation. Then, the classification process of these factors is performed using K-means algorithm. Factors that affect the learning process in order to perform the analysis of the factors affecting student learning students, teachers, the curriculum and namely social life is divided into four main sections. Artificial intelligence method was used to perform the analysis of the impact of these factors on the learning process. Thus, the determination of the factors that affect student learning and analysis will be done in an easier way. Also easily cause remedy the problems which occur in the training using the results obtained from this method is produced. Thereby more accurately and quickly determine the problems to occur in the training satisfies faster and more effective solutions can be realized.
15th International Conference on Information Technology Based Higher Education and Training (ITHET) -- SEP 08-10, 2016 -- Istanbul, TURKEY
Keywords: Artificial Intelligence; Student; Instructors; Curriculum; Social life